Exclusive Breastfeeding and Complementary Feeding Practices Are Associated with Stunting among Children Aged 6–24 Months: A Cross-Sectional Study in Sigi Regency - Fariz Syamsu Ma’arif; Evi Fitriany; Ahmad Wisnu Wardhana; Hanis Kusumawati Rahayu; Sulistiawati Sudarso (Poltekkes Kemenkes Palu, 2026)
Background: Stunting is a chronic nutrition problem associated with long-term inadequate nutrient intake and suboptimal infant and young child feeding practices, including exclusive breastfeeding and complementary feeding (MP-ASI). This study assessed the association of exclusive breastfeeding and complementary feeding practices with stunting among children aged 6–24 months in the Biromaru Primary Health Center area, Sigi Regency. Methods: This analytical cross-sectional study included 89 children aged 6–24 months selected using total sampling. Data were collected through caregiver questionnaires and anthropometric measurements. Stunting was defined as length-for-age (PB/U) z-score < −2 SD based on the CDC 2020 reference. Associations were tested using the chi-square test (α=0.05), and effect sizes are presented as prevalence ratios (PR) with 95% confidence intervals (CI). Results: The prevalence of stunting was 55.1% (49/89). Stunting was significantly associated with non-exclusive breastfeeding (67.4% vs 41.9%; PR=1.61, 95% CI 1.07–2.42; p=0.016) and early initiation of complementary feeding <6 months (80.0% vs 50.0%; PR=1.60, 95% CI 1.14–2.25; p=0.033). Among complementary feeding quality indicators, inappropriate food type (PR=1.53, 95% CI 1.08–2.17; p=0.028), texture (PR=1.55, 95% CI 1.09–2.21; p=0.022), and especially feeding frequency (64.2% vs 27.3%; PR=2.35, 95% CI 1.16–4.76; p=0.003) were associated with stunting. Portion size was not significantly associated with stunting (PR=1.22, 95% CI 0.81–1.83; p=0.322). Conclusion: In this setting, stunting was associated with non-exclusive breastfeeding and suboptimal complementary feeding practices, particularly inadequate meal frequency. Nutrition programs should prioritize strengthening exclusive breastfeeding support and improving complementary feeding practices (timely initiation at 6 months, age-appropriate frequency, food type, and texture).